Gastric-Type Endometrial Adenocarcinoma: Report of Two Cases in Patients From the United States. (June 2018) - McCarthy, Whitney A.; Makhijani, Reeva; Miller, Katherine; Rojas, Kristin; Beffa, Lindsey; Mathews, Cara; Robison, Katina; Quddus, M. Ruhul
Gastric-type adenocarcinomas of the uterine cervix have been described within the literature in detail; however, the description of gastric-type endometrial adenocarcinomas is a recent development, with only two cases originating from Japan in the world literature to date. According to these prior reports, the recognition of this pattern of differentiation is critical, as it is often associated with deep myoinvasion, positive regional lymph nodes, and poor outcome despite appropriate adjuvant treatment. We present two cases of endometrial adenocarcinoma with gastric-type differentiation in patients from the United States with superficial myoinvasion and positive patient outcomes. Gastric-type differentiation in endometrial adenocarcinomas is rare and likely underrecognized. Continued reporting of these cases is necessary to further understand the natural history and clinical implications of this entity.